Pengembangan Ekspansi Klinik Gigi Berbasis Kelayakan Finansial, Persepsi Pasien, SWOT, dan Dental Tourism: Studi Kasus Klinik BFD di Kuta Selatan - Syeni Sunendra; Agus Putu Abiyasa (Journal of Management and Creative Business, 2026)
The advancement of the dental health industry in the tourism area demands a clinic expansion strategy that is integrated between financial aspects, patient perception, market analysis, and dental tourism opportunities. This study aims to develop a model for the expansion of the BFD Clinic in South Kuta, Bali, with an applied business research approach based on descriptive quantitative case studies. Primary data was obtained through a survey of 26 patients as an initial validation of service perception, while financial data came from an internal feasibility study with an initial investment of IDR 4,045,000,000 and a 10-year projection. Financial analysis uses indicators of net present value, internal rate of return, payback period, discounted payback period, profitability index, and break-even point. The results of the moderate scenario show an NPV of IDR 8,012,663,759, IRR of 38.26%, payback period of 3.01 years, discounted payback period of 3.62 years, and PI of 2.98, with an operational BEP of 159 patients per month. Patient surveys affirm the main strengths in physician professionalism, quality of care, staff friendliness, cleanliness, comfort, and modern facilities, while areas of improvement include parking access, reservation systems, waiting times, and digital promotions. The proposed expansion model emphasizes value-based dental clinics through standardization of service quality, differentiation of painless dentistry, integration of digital systems, and hospitality referral strategies. The novelty of this research lies in the integration of financial feasibility, patient validation, market mapping, SWOT-TOWS, and dental tourism in one decision framework for dental clinic expansion.